Effect of Maturity and Environmental Conditions on Chemical Composition of Olive Oils of Introduced Cultivars in Morocco - Samira El Qarnifa; Abderraouf El Antari; Abdellatif Hafidi (Journal of Food Quality)
This work aims at evidencing the quality and chemical composition of extra virgin olive oils according to stages of maturity and in relation to the geographical location of olives. Three different olive cultivars (Moroccan Picholine, Languedoc Picholine, and Frantoio), grown in two different locations in Morocco (Errachidia and Marrakech), were studied during the two crop years (2016 and 2017) at three stages of maturity (green, purple, and black). This work has been carried out by analyzing several parameters, such as the quality characteristics (acidity and peroxide value), the chemical composition (total phenol content and fatty acid composition) of the oils, and also the fruit characteristics of the olives (maturity index, fruit water content, and oil content). The results obtained in this study indicate that as maturity advanced, there was a slight rise in oil content and acidity, while there was a decrease in fruit water content and peroxide value in both locations during the two crop years. The fatty acid composition of extra virgin olive oil showed a significant increase of linoleic acid and polyunsaturated fatty acids (PUFAs) and a decrease of oleic acid, palmitic acid, monounsaturated fatty acids (MUFAs), and MUFA/PUFA ratio as the maturation process progressed. A significant gradual decrease was noted in total phenol content and bitterness intensity from the green stage to the black. Moreover, olive oil composition differed clearly between the two sites. Therefore, the olive cultivar, harvesting date, and geographic location influence the olive oil characteristics.